Diseño de material virtual didáctico de impresión offset para la asignatura de producción gráfica en la carrera de diseño gráfico computarizado de la Universidad Técnica de Cotopaxi en el periodo 2014 - Chicaiza Caizaguano, Byron Rene (2016)
This research contains relevant information about the offset system and the total process of operation system at Technical University of Cotopaxi in graphic production system subject, the new technology usage makes the human beings improve the printing techniques every day to achieve efficiency, high quality and faster in the printing techniques, for that reason has been considered necessary to develop the virtual designing in educational material for graphic designer….